Pengaruh Kombinasi Towel Curl dan Core Exercise terhadap Peningkatan Keseimbangan Dinamis pada Anak Flat Foot Usia Prasekolah - Saskia Meidi; Atika Yulianti; Nurul Aini Rahmawati (Yayasan Literasi Sains Indonesia, 2025)
The period is marked by children who move by standing and high activity. Usually this period is called the golden age where there is a rapid increase in growth and development. The medial longitudinal arch is the largest arch of the foot, normally the longitudinal arc is caused by the pressure of body weight which is divided evenly with the entire sole of the foot. Flat foot is a problem that occurs in the arcus. The impact of children who experience flat feet is pain, balance disorders and walking. Flat foot will cause balance disorders, especially dynamic balance. This study aims to determine whether there is an effect of the combination of curl towels and core workouts on improving dynamic balance in flat feet in preschool children. This study uses quasi-experimental and uses a pre and post-test design. Samples were taken by purposive sampling as many as 66. Respondents will be given interventions in the form of curl towels and core workouts. The research instrument uses the clarke angle test and beam balance. The kolmogorov-smirnov test is used for normality testing, and the wilcoxon test for hypothesis testing. This study was conducted at Kartika Kindergarten and Bhayangkara Kindergarten.